Efektifitas Aplikasi Waktu Pemberian Biourine Plus dan Dosis Pupuk Urea Terhadap Peningkatan Pertumbuhan dan Produksi Padi (Oryza sativa L.) - Mariyatul Qibtiyah (Agriculture faculty, Darul ‘Ulum Islamic University (UNISDA) of Lamongan, 2019)
Objective of the research was to study the effect of application time of biourine plus and dosages of urea fertilizer on increasing the growth and production of rice. The research applied the Split Plot Design by 3 replications. The main plot is the application time of biourine that comprises of 2 levels: in the morning and in the afternoon. The sub plot is the dosage of urea fertilizer that comprises of 5 levels: 0, 150, 200, 250 and 300 kg ha-1. Result of the research showed a significant interaction between time of application of biourine plus and dosage of urea fertilizer on diverse-observed parameters and ages. On parameter of growth, the application time in the morning and dosage of urea fertilizer 250 kg ha-1 and application time in the morning by dosage of urea fertilizer 300 kg ha-1 could increase plant leaf, area indexs heigth, numbers of plantlet per clump, which are better than other treatments. On parameter of yield, the application time in the morning and dosage of urea fertilizer 250 kg ha-1 and application time in the morning and dosage of urea 300 kg ha-1 could increase numbers of panicle per clump and weight of harvested dry spikelets per hectare, which are better than other treatments.